Human Vision vs. Computer Vision: A Readability Study in a Virtual Reality Environment - Qing, Zhu; Edara, Praveen (2022 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops (VRW), 2022)
Text plays an important role in conveying information to users in a virtual reality (VR) environment. Both VR software and hardware are evolving rapidly to improve text display quality. However, evaluation of text readability still relies on human participants. In this study, cloud computer vision was used to evaluate text readability in VR. Human subjects were recruited to test the same text scenarios. The cloud computer vision-based approach produced results that were consistent with human vision-based recognition. The use of computer vision to automate text readability evaluation could significantly reduce the overall effort and time in developing readable text in VR.